2020
DOI: 10.11591/ijeecs.v19.i1.pp178-187
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic feature for an effective elbow-joint angle estimation based on electromyography signals

Abstract: <a name="_Hlk561743"></a><span>Some physical parameters influence the electromyography signal (EMG). when the EMG signal is used to estimate the position of the elbow. An adaptable feature was important to reduce a variation on the parameters. The aim of this paper is to estimate the joint position of the elbow using EMG signal based on a dynamic function. The major contribution of this work is that the method proposed is capable of determining the elbow position using the non-pattern (NPR) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The method is often used because of its quick and simple implementation. Time-domain features are processed without any signal transformation for the raw EMG signals and evaluated based on the value of signal amplitude that varies over time [1,22,28,30,32,33,37]. Processing of the raw data is critical to remove baseline noises, motion artifact noises, etc.…”
Section: Emg Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The method is often used because of its quick and simple implementation. Time-domain features are processed without any signal transformation for the raw EMG signals and evaluated based on the value of signal amplitude that varies over time [1,22,28,30,32,33,37]. Processing of the raw data is critical to remove baseline noises, motion artifact noises, etc.…”
Section: Emg Analysismentioning
confidence: 99%
“…On the other hand, nonpattern recognition controls are practical and often used as control schemes. The objective, in this case, is to characterize motion, gripping force, rotation of angles, and others [5,11,18,27,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Humanrobot interactions (HRI) are a wide research field. Currently, those systems are used in many applications and researches such as robot control systems [11][12][13][14][15][16][17][18][19][20][21][22][23], medical recognitions and rehabilitations [24][25][26][27], and intelligence assistive devices [5,12,15,[28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been used extensively in HGR and other EMG-related studies targeting different functionalities. Several kinds of research focusing particularly on elbow and shoulder movements have been reported in Triwiyanto et al [13], Antuvan et al [14], Martinez et al [16], Hassan, Abou-Loukh, and Ibraheem [19], Young et al [45], Jiang et al [46], and Tsai et al [47], classification of upper limb motion using extreme learning machines by Antuvan et al [39], using Support Vector Machine (SVM) [6,8,19,48], investigation of shoulder muscle activation pattern recognition using machine learning by Jiang et al [46], and detection movements using EMG signal for upper limb exoskeletons in reaching tasks by Trigili et al [49]. These papers verify the suitability of EMG signals for biopotential intelligent robot control.…”
Section: Introductionmentioning
confidence: 99%